Age-related health deficits and five-year mortality among older, long-term cancer survivors. Issue 7 (September 2022) - Leach, Corinne R.; Gapstur, Susan M.; Cella, David; Deubler, Emily; Teras, Lauren R.
Abstract: Introduction: Geriatric assessment evaluates multiple domains of health that, together, are superior to using chronologic age for predicting outcomes, such as hospitalization and mortality among patients with cancer. Most studies have not included comparison groups of individuals without cancer and assessed domains around the time of initial cancer diagnosis. Further, the potential for brief, self-reported measures to capture deficits that similarly predict mortality has not been well examined. This study compared age-related health deficit prevalence between older, long-term cancer survivors and individuals without a cancer history, and estimated associations between deficits and mortality risk among survivors. Materials and methods: Analyses included participants in the Cancer Prevention Study (CPS)-II Nutrition Cohort who were cancer-free at enrollment in 1992/1993 and completed the Patient Reported Outcome Measurement Information System® (PROMIS®) global health questionnaire in 2011. Age-related deficits in five domains (comorbidities, functional status, mental health, malnutrition/weight loss, and social support) were self-reported. Cancer information was self-reported and confirmed via medical records or state cancer registries. Vital status through 2016 and cause of death was ascertained by linkage with the National Death Index. Results: Analyses included 9979 participants (median age = 80) diagnosed with invasive cancer 5–20 years prior to completing the 2011 survey and 63, 578 participants without a cancer history (median age = 79). Overall deficits in the five domains were similar among long-term cancer survivors and controls. However, survivors of specific cancer types — non-Hodgkin lymphoma (NHL), lung, and kidney cancer – were more likely to report deficits in mental health and functional status than the control group. Among all survivors, each domain was independently associated with all-cause mortality, particularly functional status (hazard ratio [HR] = 2.02; 95% confidence interval [CI]: 1.80–2.27) and mental health (HR = 1.84; 95% CI: 1.65–2.04). Mortality risk increased with the number of deficits. Discussion: These results suggest that, several years after treatment, NHL, lung, and kidney cancer survivors are still more likely to experience age-related deficits compared to other similarly-aged individuals. Furthermore, results show that shorter, self-reported physical and mental health assessments, such as the PROMIS® global health questions, are predictive of mortality among older, long-term cancer survivors and, therefore, may be useful in clinical and research settings.